AngularJS for ASP.NET MVC developers - Romero, Brett; Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2017)
"AngularJS is one of the hottest and most in-demand web languages on the market. Be one of the only .NET developers on your team to posses this skill. If you know zero AngularJS, you're the perfect student. In this course, you'll download AngularJS straight into your brain. In time, you'll fully understand how to use AngularJS client side and how to interact with .NET. While AngularJS 2 is now available, there are a ton of AngularJS 1 applications that need to be maintained and enhanced. Companies can take a while to move to a new technology. Especially when the upgrade is as night and day as it is between AngularJS 1 & 2. Meaning, AngularJS 1 development will continue to be an in-demand skill. Beef up your resume with AngularJS. You'll not only be able to talk the talk but this course with arm you with enough hands on experience that you will also definitely walk the walk."--Resource description page.
Title from resource description page (viewed December 18, 2017).
Presenter, Brett Romero.
Keywords: AngularJS (Software framework); Web applications; Application software -- Development; Software frameworks; Electronic books